Student Power! The Radical Days of the English Universities. - Hanna, Esmée Sinéad (Cambridge Scholars Publishing, 2013)
Student Power! The Radical days of the English Universities is an original contribution to the exploration and understanding of the radicality of the English student movement of the 1960s. This movement was significant and widespread within English universities, and occurred within the context of global student unrest. The research, on which this book is founded, brings together two key data sources, documents and oral history interviews, presenting previously unpublished and original researc ...